Knock-Out of Retrovirus Receptor Gene Tva in the Chicken Confers Resistance to Avian Leukosis Virus Subgroups A and K and Affects Cobalamin (Vitamin B12)-Dependent Level of Methylmalonic Acid - Koslová, Anna; Trefil, Pavel; Mucksová, Jitka; Krchlíková, Veronika; Plachý, Jiří; Krijt, Jakub; Reinišová, Markéta; Kučerová, Dana; Geryk, Josef; Kalina, Jiří; Šenigl, Filip; Elleder, Daniel; et al. (Viruses, 2021)
The chicken Tva cell surface protein, a member of the low-density lipoprotein receptor family, has been identified as an entry receptor for avian leukosis virus of classic subgroup A and newly emerging subgroup K. Because both viruses represent an important concern for the poultry industry, we introduced a frame-shifting deletion into the chicken tva locus with the aim of knocking-out Tva expression and creating a virus-resistant chicken line. The tva knock-out was prepared by CRISPR/Cas9 gene editing in chicken primordial germ cells and orthotopic transplantation of edited cells into the testes of sterilized recipient roosters. The resulting tva -/- chickens tested fully resistant to avian leukosis virus subgroups A and K, both in in vitro and in vivo assays, in contrast to their susceptible tva +/+ and tva +/- siblings. We also found a specific disorder of the cobalamin/vitamin B12 metabolism in the tva knock-out chickens, which is in accordance with the recently recognized physiological function of Tva as a receptor for cobalamin in complex with transcobalamin transporter. Last but not least, we bring a new example of the de novo resistance created by CRISPR/Cas9 editing of pathogen dependence genes in farm animals and, furthermore, a new example of gene editing in chicken.
Keywords: tva; Receptors, Virus; editace genu; Frameshift Mutation; kur domácí; Avian Leukosis Virus; Chickens; genový knockout; Female; Methylmalonic Acid; virus ptačí leukózy; kyselina methylmalonová; gene editing in chicken; ptačí proteiny; Chick Embryo; Gene Editing; virové receptory; vitamin B12/cobalamin; mužské pohlaví; zvířata; ženské pohlaví; kuřecí embryo; Animals; Male; Gene Knockout Techniques; avian leukosis virus subgroups A/K; Vitamin B 12; posunová mutace; vitamin B 12; Avian Proteins